A Class Act: An Illustrated History of the Labour Movement in Newfoundland and Labrador - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1988)
This article reviews the book, "A Class Act: An Illustrated History of the Labour Movement in Newfoundland and Labrador," by Bill Gillespie.